Encyclopedia of Leisure and Outdoor Recreation - Jenkins, John; Pigram, John (Routledge, 2003)
This is a key reference guide for the exploration of leisure and outdoor recreation. It reflects the multidisciplinary nature of these fields and contextualizes the leading research and knowledge on key concepts, theories and practices. Edited by leading authorities in the field, this volume includes a comprehensive index, and up-to-date suggestions for further reading. It is an essential resource for teaching, an invaluable companion to independent study, and a solid starting point for wider subject exploration.